IT in Banks: Emerging Trends - Rao (Katuri Nageswara); Pahuja (Yashpaul) Ed. ("52, Nagarjuna Hills,Hyderabad - 500 082", 2005)
Information Technology ; Banking
50
Keywords: Information Technology ; Banking